The nexus international terrorism and drug trafficking from Afghanistan - Shanty, Frank 1950- (a Praeger books online, 2011)
This book examines the specific issue of whether or not there is a nexus (link or point of convergence) between international opium and heroin trafficking and terrorist networks operating in or from Afghanistan. Since 9/11 many public officials and others have made definitive statements concerning an alleged nexus between criminal narcotics trafficking and terrorist networks in Afghanistan. Although some anecdotal and circumstantial evidence suggests that a linkage between drug traffickers and international terrorists may exist in Afghanistan, the question is whether a convincing case based on sound empirical data can be made regarding a nexus or linkage between Afghan-based terrorists and national or internationally-based drug traffickers